Insomnia Symptoms Among Hospice Family Caregivers: Prevalence and Association with Caregiver Mental and Physical Health, Quality of Life, and Caregiver Burden. (May 2023) - Starr, Lauren T.; Washington, Karla; McPhillips, Miranda V.; Pitzer, Kyle; Demiris, George; Oliver, Debra Parker
Background: Poor sleep exacerbates mental health problems and reduces quality-of-life (QOL) but prevalence of insomnia symptoms among hospice family caregivers and associations of poor sleep with caregiver health and QOL outcomes are not known. Objective: To describe prevalence of insomnia symptoms among hospice family caregivers and compare anxiety, depression, self-rated health, QOL, and caregiver burden between hospice family caregivers with and without insomnia symptoms. Methods: Descriptive sub-study using data collected during baseline interviews of hospice family caregivers involved in a randomized clinical trial in Midwestern United States (xxxxxxxx). Caregivers were dichotomized based on Insomnia Severity Index (ISI) scores (8+ indicated insomnia symptoms). Results: Among 57 hospice family caregivers, the mean ISI score was 8.2; nearly half (49.1%) experienced insomnia symptoms. Compared to caregivers without insomnia symptoms, caregivers with insomnia symptoms reported 2.4 times greater mean anxiety scores (4.7 vs 11.4); 3.5 times greater mean depression scores (3.1 vs 10.7); 2.1 times greater caregiver burden scores (5.6 vs 11.8); and 1.3 times lower self-rated health (3.5 vs 2.8); 1.3 times lower total QOL scores (29.3 vs 22.6); including differences in emotional QOL (7.9 vs 2.2), social QOL (7.2 vs 3.0), and physical QOL (7.4 vs 5.3). Conclusions: Hospice family caregivers experience high prevalence of insomnia symptoms; caregivers with insomnia symptoms report worse anxiety, depression, caregiver burden, QOL, self-rated health. Clinicians must screen hospice caregivers for poor sleep and mental health and offer supportive interventions that improve their sleep and health. Policy makers must expand hospice benefits to better support family caregivers.